Single Molecule Method for Molecular Biology - Jeong Hee, Kim; 정철현 (대한구강생물학회, 2018)
In order to understand biological phenomena accurately, single molecule techniques using a physical research approach to molecular interactions have been developed, and are now widely being used to study complex biological processes. In this review, we discuss some of the single molecule methods which are composed of two major parts: single molecule spectroscopy and manipulation. In particular, we explain how these techniques work and introduce the current research which uses them. Finally, we present the oral biology research using the single molecule methods.